Investigating Farmer Perspectives and Compost Application for Soil Management in Urban Agriculture in Mwanza, Tanzania - Esmail, Shefaza; Oelbermann, Maren (Frontiers in Soil Science, 2022)
African countries are urbanizing at a rapid rate. Research on urban agriculture may be key to ensuring urban food and soil security. This study aimed to evaluate pathways for integrated soil fertility management using a mixed methods approach to consider both social perspectives and soil quality in the city of Mwanza, Tanzania. The social component of urban agriculture was explored using semi-structured interviews with urban farmers (n=34), through judgement and snowball sampling. Qualitative analyses showed that urban farmers range in age and gender, as well as in experiences and cultivation practices, though all use hand tools. Farmers reported reliance on rainy seasons for cultivating. However, farmers also raised concerns about a changing climate and unpredictability of rain, which impacts crop productivity. Most interviewed farmers (82%) would like to improve their soils, and many use manure as an amendment stating that animal manure is the best way to improve soil. Additionally, most urban farmers (62%) have not tried any form of food waste compost but responded positively to try it if they had access and were taught how to use it. For the second aspect of this study a field trial was conducted to evaluate and compare the effects of organic and inorganic amendments on soil quality and crop productivity over the short-term. The results from the field trial determined that organic amendments (poultry manure and food waste compost) improved soil water holding capacity by 14 to 19% and enhanced microbial biomass 1.7 to 4 times compared to treatments with inorganic nitrogen fertilizer. Crop productivity with organic amendments was comparable to that in treatments with nitrogen fertilizer. We conclude that urban agriculture is an integral aspect of Mwanza City, and the application of organic amendments improves urban soil quality compared to the application of inorganic fertilizer, which has implications for urban soil security, land use planning, and food sovereignty in developing countries.